Soveršenstvovanie sportivnych dviženij na osnove smart-technologij iskusstvennoj aktivacii myšc - Rostovtsev, V. L.; Kryazhev V. D. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In the article results of long-term researches of possibilities of management of movements of sportsmen on the basis of artificial activation of muscles are resulted with the purpose of increase of sports productivity. It is shown that artificial activation of muscles with the help of devices of dynamic electrostimulation, carried out at the most crucial moments of sport movement, increases the output mechanical power with decreasing metabolic costs, which is manifested in increasing the efficiency and economy of movement in speed skating, bicycle pedaling, ski racing. Athletes exceeded the maximum speed and showed the best result at a distance by reducing the oxygen cost of a meter of track. After a series of training sessions, the generated motor skill is preserved, which is manifested in improving the sporting result in the competitions. To use this method in the natural conditions of training, a smart technology for improving sports movements has been developed, implemented on the basis of a special mobile application for a smartphone and a hardware-programmed complex mounted in sports equipment. The test of this technology for the process of training qualified athletes has revealed the convenience of its use and efficiency, which was manifested in improving sports performance in the race for roller skis and track and field athletics.